The Impact of Social Responsibility Activities on Gaining Values - Sümeyye Koç (Yakın Doğu Üniversitesi İslam Tetkikleri Merkezi Dergisi)
Social responsibility is one of the most critical issues expected to be included in education programs today, as the need for socially responsible individuals is ever-increasing. Education is vital in transferring values to students that align with societal ideals. Teachers are the most essential component of values education and transmission, since teachers are the ones who represent and lead values education. It is stated that values education programs carried out through social activities significantly affect the social skills of individuals. In this context, teachers who attach importance to and model social skills will contribute positively to their students’ social skills. Students are considered to learn more through extracurricular educational experiences than through experiences in the traditional classroom. This also applies to teacher candidates. In this regard, the university is critical in terms of the effectiveness of institutions that train teacher candidates, who will in turn impact the future by teaching new generations. The teacher candidates cannot learn these abilities solely through formal schooling. Hence, individual effort and research, participation in group activities, and getting support from non-governmental organizations (NGOs) are now essential to learn the skills. This study, which was prepared based on this approach, is based on the findings of several social responsibility exercises for future teachers as part of the “Teachers of the Future Project”. Social responsibility activities implemented within the scope of the project that has been carried out can be summed up as teacher candidates engaging in educational activities for the underprivileged, marking down the positive experiences that experienced teachers have had throughout their careers, meeting with secondary and high school students during social activities and informing them about the universities and departments they are currently enrolled in. The social responsibility activities in this project aim to increase teacher candidates' sense of responsibility. This research aims to reveal the effect of this project, which teacher candidates participated in, on their acquisition of values. Accordingly, the study aims to investigate the impact of the social responsibility activities that teacher candidates participate in within the project’s scope on gaining the necessary skills for values education and the social responsibility activities they will implement while teaching. The study used an experimental methodology and involved 174 teacher candidates enrolled in several university departments in the Turkish Republic of Northern Cyprus in 2021. The research used two scales and a semi-structured interview form to reveal the effect of social and cultural activities on the acquisition of values. The research’s findings showed that the teacher candidates’ participation in social responsibility projects led to considerable improvements in their values, which are believed to be associated with social responsibility. These values are honesty, responsibility, patience, respect, helpfulness, unity, patriotism, and the importance of family. The increase in these values shows that the collaborative and project-based training and practices organized within the scope of values education are effective. One of the most important results of the research is that education, activity and project-based practices applied beyond the courses in the faculty increase the acquisition of values of teacher candidates. In addition, it has been revealed that values acquisition is more effective and higher for teacher candidates who have participated in similar practices and training before. The reason for this is a reflection of previous positive experiences. In the interviews, pre-service teachers said that the social responsibility activities they participated in within the project’s scope led to an awareness of values education and positively affected the acquisition of values. Another result that emerged from the interviews was the statement that it was beneficial for them to see model applications. In addition, if they are still university students, they also said that participating in activities with secondary school students gave them an empathetic perspective. Pre-service teachers emphasized that thanks to the project, they developed both personally and professionally, and could better understand students and find the correct methods. It may be suggested that in addition to their formal education at the university, teacher candidates take part in unofficial training, social responsibility initiatives, and values-based activities. In addition, it is recommended that university teacher training departments carry out more joint projects with other educational institutions and NGOs that provide education-related services and even include these activities in their training programs.